Controlled Release of Doxorubicin from Doxorubicin/γ-Polyglutamic Acid Ionic Complex. (13th May 2010) - Manocha, Bhavik; Margaritis, Argyrios
Abstract : Formation of drug/polymer complexes through ionic interactions has proven to be very effective for the controlled release of drugs. The stability of such drug/polymer ionic complexes can be greatly influenced by solution pH and ionic strength. The aim of the current work was to evaluate the potential of γ -polyglutamic acid (γ -PGA) as a carrier for the anticancer drug, Doxorubicin (DOX). We investigated the formation of ionic complexes between γ -PGA and DOX using scanning electron microscopy, spectroscopy, thermal analysis, and X-ray diffraction. Our studies demonstrate that DOX specifically interacts with γ -PGA forming random colloidal aggregates and results in almost 100% complexation efficiency. In vitro drug release studies illustrated that these complexes were relatively stable at neutral pH but dissociates slowly under acidic pH environments, facilitating a pH-triggered release of DOX from the complex. Hydrolytic degradation of γ -PGA and DOX/γ -PGA complex was also evaluated in physiological buffer. In conclusion, these studies clearly showed the feasibility of γ -PGA to associate cationic drug such as DOX and that is may serve as a new drug carrier for the controlled release of DOX in malignant tissues.